REGIONAL FEATURES OF THE USE OF GROUNDWATER AS A POTENTIAL SOURCE OF THE FORMATION OF THE RADIATION FACTOR - E. V. Lisachenko; N. A. Koroleva (Радиационная гигиена)
Underground water is one of the sources of water supply and the most important mineral resources. The enrichment of natural groundwater with radium isotopes is a geochemical regularity, and their use a recognized source of additional exposure to the population and the environment. Forecast resources of groundwater in the territory of the Russian Federation are 869055 thousand m3/day. As of 01.01.2015, 15054 deposits (sections) of groundwater have been explored, of which 10556 are in operation. In the federal districts, the volume of extraction and extraction of groundwater varies widely. The percentage of groundwater in domestic and drinking water supply in 35 regions of the Russian Federation ranges from 70 to 100%; in more than 30 regions it exceeds 90%. A whole series of large cities provide water supply through the underground water. Underground waters, depending on the field of application, are divided into drinking, technical, heat power, industrial and medical. The formation of numerous areas with an increased content of natural radionuclides for all types of groundwater is largely determined by the volume of their use. Organized use of groundwater is preceded by special water treatment, where it is possible to form doses of exposure to those above permissible levels established in NRB-99/2009 and the formation of a mass of waste with an increased content of natural radionuclides. In many regions of the country, there is a prospect of a constant increase in the use of all types of groundwater and the creation of new enterprises, which will require monitoring and radiation and hygienic assessment. Particular attention should be paid to the use of associated waters of oil and gas fields that have the highest content of natural radionuclides among groundwaters as a promising source of mineral raw materials.